Mass Media and Their Relationship with Criminal Law in Albania - Kastrati, Rovena (European Journal of Multidisciplinary Studies, 2016)
Information is the currency of democracy. (Thomas Jefferson), Freedom of expression is part of the so-called "negative liberty" that imply their guarantee by the Constitution as inviolable and for their realization require non-interference by the state or by private entities. Media uses this freedom, to achieve its objectives where not rarely goes beyond violating the other rights and freedoms prescribed in the Constitution. The power that people gave to media has made it a powerful pressure weapon, but often also a victim of its "sacred" mission, that of informing public about everything that happens. The aim of this paper is to present media reports with criminal law, which are dualistic reports: approaching and contradictory. It will also be presented an overview of the situation in Albania, where the media and its influence play a significant role in people's opinion and in the progress of criminal proceedings. In the first part of the paper I have mentioned the central role of the media in democracy and the benefits that community and society receives from media's freedom. Furthermore, in the second part l have been focusing on the other side of the coin addressing key points in which the media is presented as violating the human rights and interfering in criminal proceedings. In the third and last part I have submitted the role of investigative journalism as an important link in the media but in Albania is still unconsolidated.
Keywords: media, prevention of criminality, exceeding of powers, personal integrity violation, intrusion in the criminal process.